Impact of the Spanish model of school management on the professional identity of school leaders - Bolívar, Antonio; Ritacco, Maximiliano (Education Policy Analysis Archives, 2016)
Spain presents a unique school management model: a teacher chosen by his own workmates (teachers) exercises the management of the school, and after this term of management (4-8 years), returns to the teacher staff. Such an itinerary of “back and forth” presents a series of duplications in identity: manager or leader; representative of the Administration and/or teaching colleagues; accountability agent and/or pedagogical agent; etc. This paper reviews the literature on management identity, especially under the ISSPP (International Successful School Principals Project), as well as the characteristics of the Spanish management model. Methodologically, from a biographical-narrative perspective, the study looks to understand the impact of the Spanish model of school management upon the identity of the principals through content analysis of the testimony of 15 school principals (in depth interviews). As a result of the data categorization process, a group of categories emerged: Personal identity; Professional identity (internal perspective); Professional identity (external perspective); Social identity; Professionalization; [and] Double identity – that reference those dimensions of the school principals’ identity impacted by the Spanish school management model. Finally, fragments and excerpts extracted from the interviewed testimonies are used in order to advance in the narrative and interpretative construction of the study (grounded theory).